Implementation and Verification of a Wi-Fi Ad Hoc Communication System in an Underground Mine Environment - Ikeda, H.; Kawamura, Y.; Tungol, Z.P.L.; Moridi, M.A.; Jang, Hyong Doo (Springer Nature, 2020)
Wireless sensor networks WI-Fi ad hoc have been proposed information transmission between data loggers and mobile station (smartphones). The wireless data transmission follows from an underground station to a worker’s smartphone and, then, after the worker has left the mine, to a data logger on the surface. The serviceability of this system was tested by measurement of communication quality indexes in various environments. The tests show that wireless communication between a stationary point and a mobile devise is possible at transfer speeds up to 2 MB/s with a packet error rate (PER) below 25% either at a maximum distance of 110 m in a straight path or at a distance of 20 m in case of a corner or turn of the path. The proposed system allows the transmission of 39.6–79.2 MB of monitoring data to a worker moving at 20 km/h.